HUBUNGAN KEJADIAN PERUNDUNGAN DENGAN KEMAMPUAN INTERAKSI SOSIAL PADA REMAJA DI SMP MUHAMMADIYAH 9 WATUKEBO - Amanda Eka Saputri Saputri; Mad Zaini; Komarudin (ASSYIFA : Jurnal Ilmu Kesehatan, 2026)
Bullying is a form of aggressive behavior repeatedly directed toward individuals who are perceived as weaker and may negatively affect adolescents’ psychosocial development, including their social interaction skills in the school environment. This study aimed to determine the relationship between bullying incidents and social interaction skills among adolescents at SMP Muhammadiyah 9 Watukebo. This quantitative analytic study employed a cross-sectional design. The population consisted of 246 students in grades VII and VIII, with 152 respondents selected using purposive sampling based on the inclusion criteria. Data were collected using the Olweus Bully/Victim Questionnaire and a social interaction skills questionnaire with a Likert scale. Data were analyzed using the Spearman Rho test with a significance level of 0.05. The results showed a significant relationship between bullying incidents and social interaction skills, with a p-value of 0.001 and a correlation coefficient of -0.258. It can be concluded that there is a negative relationship between bullying incidents and social interaction skills, indicating that higher bullying incidents are associated with lower social interaction skills among adolescents.